The interactive effects of emotional leadership and resilience on job satisfaction and organizational commitment among Korean youth sports instructors - Jung, Myung Kyu; Jung, Tae Gyeom; Kang, Yu Jin; Jeong, Kwon-Hyuk (Frontiers in Psychology, 2025)
IntroductionThis study aims to provide practical insights into developing intervention strategies to enhance organizational effectiveness in Korean youth physical education facilities. Specifically, it investigates the interactive effects of resilience and emotional leadership on job satisfaction and organizational commitment.MethodsTo address this aim, data were collected from 205 physical education instructors employed at Korean youth physical education facilities in 2024. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).ResultsThe analysis revealed a statistically significant interaction effect between resilience and the personal competency dimension of emotional leadership on job satisfaction.DiscussionThese findings provide a theoretical foundation for understanding the dynamic interaction between emotional leadership and resilience. Additionally, the results offer practical implications for developing effective human resource management strategies tailored to the unique organizational environment of Korean youth physical education facilities.